The Bornholm intermediate waters: Origination, pathway, and detection within the cold intermediate layer of the Baltic Sea. (January 2023) - Bukanova, Tatiana; Lobchuk, Olga; Chubarenko, Irina
Highlights: Early-spring cold waters of western Baltic Sea areas plunge to intermediate layers. They constitute the core of the Cold Intermediate Layer of the Baltic Proper. Density gradient and wind action are the drivers. Abstract: The Cold Intermediate Layer (CIL) is a distinctive feature of the Baltic Sea thermohaline structure: it is evident annually from March to December between the upper freshened layer and the deep layer with saline waters of oceanic origin. Water parameters are vertically inhomogeneous within the CIL, reflecting a complicated process of its formation that hasn't been exhaustively described yet. On the base of field measurements and remote sensing data, a detailed study of the CIL formation in spring 2006 was performed. It showed that the core of the CIL (the coldest water) has a specific T, S-index that indicates the source of these waters in the south-western part of the sea. The data of CTD measurements, satellite-derived sea surface temperature (SST), and meteorological information were used to distinguish and trace the CIL core waters. The abrupt transformation of the SST field was observed in March 2006 when the coldest waters (0.9–2.1 °C) of moderate salinity (7.6–8.1) plunged from the upper mixed layer in the vicinity of Bornholm Island into intermediate layers. These waters were later identified as the sublayer of the CIL in the Baltic Proper in April and May 2006. The drivers of the penetration of winter-cold surface waters into the intermediate layers are suggested to be the negative surface buoyancy flux due to warming of cold surface waters with temperature below that of the density maximum and the intensification of easterly winds. Considering the importance of the CIL formation process for the entire Baltic Sea conveyor belt, these CIL core waters were termed the Bornholm Intermediate Waters (BIW). The T, S-index of the BIW shall vary from year to year, reflecting the severity of the past winter and the conditions of the particular spring. However, the BIW location right above the pycno/halocline, the lowest (specific for the current year) water temperature and its characteristic salinity of 7.6–8.1 are repeatedly confirmed by field observations in the Baltic Proper in spring. Joint application of satellite observations, field measurements, and meteorological data provides a coherent view on the process of the BIW waters origination. The results are particularly important it the context of growing hypoxia of deep Baltic waters, providing evidence of the mechanism of seasonal ventilation of intermediate water layers.